International trends in hepatocellular carcinoma incidence, 1978–2012. Issue 2 (5th November 2019) - Petrick, Jessica L.; Florio, Andrea A.; Znaor, Ariana; Ruggieri, David; Laversanne, Mathieu; Alvarez, Christian S.; Ferlay, Jacques; Valery, Patricia C.; Bray, Freddie; McGlynn, Katherine A.
Abstract : Primary liver cancer, the major histology of which is hepatocellular carcinoma (HCC), is the second leading cause of cancer death worldwide. We comprehensively examined recent international trends of primary liver cancer and HCC incidence using population‐based cancer registry data. Incidence for all primary liver cancer and for HCC by calendar time and birth cohort was examined for selected countries between 1978 and 2012. For each successive 5‐year period, age‐standardized incidence rates were calculated from Volumes V to XI of the Cancer Incidence in Five Continents (CI5) series using the online electronic databases, CI5 plus . Large variations persist in liver cancer incidence globally. Rates of liver cancer remain highest in Asian countries, specifically in the East and South‐East, and Italy. However, rates in these high‐risk countries have been decreasing in recent years. Rates in India and in most countries of Europe, the Americas and Oceania are rising. As the population seroprevalence of hepatitis B virus (HBV) continues to decline, we anticipate rates of HCC in many high‐risk countries will continue to decrease. Treatment of hepatitis C virus (HCV) is likely to bring down rates further in some high‐rate, as well as low‐rate, countries with access to effective therapies. However, such gains in the control of liver cancer are at risk of being reversed by the growing obesity and diabetes epidemics, suggesting diabetes treatment and primary prevention of obesity will be key in reducing liver cancer in the longer‐term. Abstract : What's new? A new analysis of worldwide trends reveals that, between 1978 and 2012, liver cancer rates fell in east Asia and Italy, but rose in India, Europe, and the Americas. In this report, the authors analyzed 35 years of liver cancer incidence, the second leading cause of cancer death worldwide. Using data from the CI5plus database, they calculated incidence rates for 5 year intervals. Although liver cancer rates remained high in east Asia and Italy, they decreased, and are expected to continue to decline as HBV prevalence declines. However, liver cancer rates rose elsewhere, possibly due to increased obesity and diabetes.